Empirical difficulties in the approach to the so-called aspectual se: diachronic evidence in rioplatense Spanish - Oliver, José María (2022)
In this paper we deal with constructions that contain the so-called aspectual se in Spanish in order to determine whether the properties associated with these constructions are reflected in historical data of American Spanish. Taking as a starting point the observations of De Benito (2021) on data from peninsular Spanish from the COSER corpus, we show that the theoretical-practical difficulties in the study of this phenomenon are not exclusive to current Spanish nor to peninsular Spanish, but are evident in data from American Spanish from a diachronic perspective. By collecting data from the CORDIAM corpus, we illustrate instances of aspectual se in the Spanish of the Río de La Plata (Argentina and Uruguay) from the 16th-19th centuries. We conclude that the most widespread analyses are based on a series of strict contrasts and (a)grammaticality tests that are not necessarily reflected in the observed diachronic data. This is one of the central reasons why studies of aspectual se have not been able to arrive at a definitive approach to the data, with tools that cannot be extended to all cases.